ESRA19-0335 Costoclavicular brachial plexus block reduce hemidiaphragmatic paralysis: retrospective observational study. (30th August 2019) - Hong, B; Yun, S; Kim, B; Ko, Y; Kim, YH
Abstract : Background and aims: Hemidiaphragmatic paralysis (HDP) due to inadvertent phrenic nerve palsy is a well-recognized complication of supraclavicular block (SCB). the HDP incidence during the newly defined costoclavicular block (CCB, infraclavicular block at the costoclavicular space) has not yet been evaluated. Thus, we performed a retrospective case control study in order to compare the incidence of HDP in CCB with SCB. Methods: 315 patients, who underwent orthopedic surgery under brachial plexus block between January 2018 and December 2018, were divided into two groups, the CCB group (n=118) and the SCB group (n=197). 118 patients were selected in the SCB group by 1:1 propensity score matching. the level of the diaphragm on the block ipsilateral side was measured based on the opposite diaphragm using pre-, post-operative chest X ray images. the primary outcome, HDP was defined as a postoperative elevation of the diaphragm greater than 20 mm. Postoperative SpO2 on room air and any respiratory symptoms were also evaluated. Results: 3 (2.5%) patients in the CCB group versus 46 (39.0%) in the SCB group had HDP (P<0.001; odd ratio, 0.041 [95% confidence interval, 0.012–0.136]). There was no significant difference in postoperative SpO2 on room air . Chest discomfort or tightness was reported 4 patients in SCB group (3.4%). Not only approach method of BPB but also injected volume were significantly associated with HDP. Conclusions: The costoclavicular block significantly reduces HDP. Our results suggest that CCB may be considered for brachial plexus blocks in selected patients with pulmonary comorbidities.